Perception of stiffness trend in city residential buildings (2019)
In this project, a descriptive research was carried out in order to analyze, evaluate and detail the behavior of buildings between 4 and 18 floors of residential use in the City of San José de Cúcuta, Colombia, at the moment they are subjected to forces produced by earthquakes. For this purpose, a sample of 40 buildings framed in the above-mentioned characteristics was used by means of the SAP 2000 software. The seismic analysis of each building was made and the displacements of these were obtained when they are submitted before an earthquake. With this information, it was possible to calculate the drifts and evaluate them based on the requirements that determine the stiffness conditions present in the buildings. Finally, a document was drawn up identifying those buildings that are susceptible to significant damage in the event of a seismic movement and recommendations, due to the fact that they represent a social risk.